A Retrospective Review of the Use of Regional Citrate Anticoagulation in Continuous Venovenous Hemofiltration for Critically Ill Patients - Anne Kit-Hung Leung; Hoi-Ping Shum; King-Chung Chan; Stanley Choi-Hung Chan; Kang Yiu Lai; Wing-Wa Yan (Critical Care Research and Practice)
Background. The emergence of a commercially prepared citrate solution has revolutionized the use of RCA in the intensive care unit (ICU). The aim of this study was to evaluate the safety profile of a commercially prepared citrate solution. Method. Predilution continuous venovenous hemofiltration (CVVH) was performed using Prismocitrate 10/2 at 2500 mL/h and a blood flow rate of 150 mL/min. Calcium chloride solution was infused to maintain ionized calcium within 1.0–1.2 mmol/L. An 8.4% sodium bicarbonate solution was infused separately. Treatment was stopped when the predefined clinical target was reached or the filter clotted. Result. 58 sessions of citrate RCA were analyzed. The median circuit lifetime was 26.0 h (interquartile range IQR 21.2–44.3). The percentage of circuits lasting more than 12 h, 24 h, and 48 h was 94.6%, 58.9%, and 16.1%, respectively. There was no incidence of hypernatremia and median pH was <7.5. Hypomagnesemia and hypophosphatemia were detected in 41.6% and 17.6% of blood samples taken, respectively. Although 16 episodes had a total calcium/ionized calcium (total Ca/iCa) >2.5, only four patients had evidence of citrate accumulation. Conclusion. The commercially prepared citrate solution could be used safely in critically ill patients who required CVVH with no major adverse events.